2018
DOI: 10.1038/s41467-018-07308-5
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry formation in EBV-associated epithelial malignancies

Abstract: Epstein-Barr virus (EBV)-associated epithelial cancers, including nasopharyngeal carcinoma (NPC) and approximately 10% of gastric cancers, termed EBVaGC, represent 80% of all EBV-related malignancies. However, the exact role of EBV in epithelial cancers remains elusive. Here, we report that EBV functions in vasculogenic mimicry (VM). Epithelial cancer cells infected with EBV develop tumor vascular networks that correlate with tumor growth, which is different from endothelial-derived angiogenic vessels and is V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 60 publications
(88 reference statements)
3
126
0
1
Order By: Relevance
“…Thus tumor cells and tissues obtain blood supply [2,40]. The criteria of the VM structure are as follows: (1) absence of vascular endothelial cells on the inner wall of the VM blood vessel; (2) vascular-like channels are lined with tumor cells; (3) positive for PAS staining but negative for CD31 staining, while the endothelial vascular channels are negative for PAS staining but positive for CD31 staining; (4) erythrocytes in the vascular-like channels [44,45]. Patient-derived xenografts models have been used to dissect the mechanisms responsible for VM and tumor progression.…”
Section: Different Forms Of Tumor Angiogenesismentioning
confidence: 99%
“…Thus tumor cells and tissues obtain blood supply [2,40]. The criteria of the VM structure are as follows: (1) absence of vascular endothelial cells on the inner wall of the VM blood vessel; (2) vascular-like channels are lined with tumor cells; (3) positive for PAS staining but negative for CD31 staining, while the endothelial vascular channels are negative for PAS staining but positive for CD31 staining; (4) erythrocytes in the vascular-like channels [44,45]. Patient-derived xenografts models have been used to dissect the mechanisms responsible for VM and tumor progression.…”
Section: Different Forms Of Tumor Angiogenesismentioning
confidence: 99%
“…And phosphorylation of forkhead box protein O1 (FoxO1), which is transferred from the nucleus to the cytoplasm, prevents FoxO1 from acting on HIF-α (Fig. 1 b) [ 19 , 69 ]. Recent studies have shown that up-regulated expression of interleukin-1β (IL-1β) secreted by B cells promotes the activation of HIF-2α, and HIF-2α activation further promotes the activation of delta like canonical Notch ligand 4 (DLL4) signaling, and finally interact with neurogenic locus notch homolog (Notch) to form the IL-1β/HIF-2α/Notch 1 axis [ 70 ].…”
Section: Canonical and Non-canonical Regulation Of Hif Signalingmentioning
confidence: 99%
“…They also employed whole-genome, transcriptome, and epigenome sequence analyses of EBVinfected or noninfected AGS cells together with primary samples to comprehensively reveal that EBV infection alters host gene expression through methylation and affects five prominent networks [153]. Apart from the methylation of host cells, EBV could promote vasculogenic mimicry formation, a new tumor vascular paradigm independent of endothelial cells, in NPC and GC cells through the PI3K/ AKT/mTOR/HIF-1α axis [154].…”
Section: Genetic and Epigenetic Abnormalities Of Host Cells In Ebvagcmentioning
confidence: 99%